Pelaksanaan Pembelajaran pada Anak Tunagrahita di SLB-C YPPALB Kota Magelang - Rahayu, Anisa Sri; Puspitarini, Aulia; Erlina, Dwi; Imaniar, Neni; Wardana, Aditia Eska (Prosiding University Research Colloquium, 2022)
This study aims to find information and determine the management of learning in Children with Special Needs Tuna Grahita at SLB C YPPALB Magelang City. This research is a qualitative research with a descriptive approach which is carried out by collecting instrument data through observation, interviews, and documentation. The subjects of this study were teachers of grades IV and V. The results showed that: there were 80 students who were able to learn and 3 students with autism. This is evidenced by the acquisition of the learning implementation of mentally retarded children. Learning management strategies for mentally retarded children at SLB-C YPPALB Magelang City use various forms of methods including through direct learning activities, habituation, giving examples of exemplary attitudes by teachers. Factors supporting the implementation of education for Children with Special Needs are adequate facilities and infrastructure, understanding from teachers to students through learning activities that are quite good, as well as good support from the surrounding community and government. While the obstacle is the character possessed by each student.